2016
DOI: 10.1007/s00508-016-0973-1
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional left atrial volume index is correlated with P wave dispersion in elderly patients with sinus rhythm

Abstract: In elderly patients, 3-dimensional left atrial volume index showed a better correlation with P wave dispersion and might be helpful in discriminating patients with prolonged P wave dispersion, who might be prone to atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Elansary et al [27] reported that PWd and LAVI were the most significant independent predictors of paroxysmal atrial fibrillation in patients with non-hemorrhagic stroke. Another study that investigated the relationship between 3D left atrial volumes and PWd found that PWd was significantly correlated with 3D-LAVImin and LAVImax [28]. In the current study, cirrhotic patients had increased PWd compared to the control subjects.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Elansary et al [27] reported that PWd and LAVI were the most significant independent predictors of paroxysmal atrial fibrillation in patients with non-hemorrhagic stroke. Another study that investigated the relationship between 3D left atrial volumes and PWd found that PWd was significantly correlated with 3D-LAVImin and LAVImax [28]. In the current study, cirrhotic patients had increased PWd compared to the control subjects.…”
Section: Discussionsupporting
confidence: 54%
“…In the group of cirrhosis patients, 40% (n: 20) had ascites, 20% ( n = 10) had hepatic encephalopathy, 80% ( n = 40) had esophageal varices, and 38% ( n = 19) were evaluated as having decompensated cirrhosis. The median Child–Pugh score was 6.0 [5–13], and the MELD score was 10.0 [6–29]. In terms of Child–Pugh disease classification, the patients were evaluated as follows; 57% child A, 28.5% child B and 14.5% child C. Non-selective beta-blockers were being taken by 60% of the patients, diuretics (furosemide, spironolactone) by 58%, antihypertensive drugs by 26% and insulin treatment for DM by 14%.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter index is measured by both 2-dimensional and 3-dimensional echocardiography and categorized as normal when ≤ 34 mL/m 2 or mild increased (35–41 mL/m 2 ; moderate, 42–48 mL/m 2 ; severe, ≥ 49 mL/m 2 . Consequently, PWD might be helpful in discriminating patients prone to PAF [57].…”
Section: Measurement Of P-wave Dispersionmentioning
confidence: 99%
“…Increased Pd has been found to be an independent predictor of PAF in patients with normal left atrial size and is proposed to occur due to changes within the atrial microarchitecture that increase the heterogeneity in sinus impulse conduction, which may occur before changes in LA dimensions [ 64 ]. Associations between left atrial size and Pd have been identified in patients with normal sinus rhythm [ 65 ] and PAF [ 64 ]. However, other studies on athletes have found no such association with atrial size [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%